Effect Of Liquid Organic Fertilizer Doses And Rhizoctonia Binuclate Fungi On The Growth Of Vanilly Seedlings (Vanilla Planifolia Andrews) - Hidayanto, Arif; Haryuni; Wiyono; Suprapti, Endang (Agribusiness Department, Agriculture Faculty, Tunas Pembangunan University, Surakarta, Indonesia, 2025)
Vanilla (Vanilla planifolia Andrews) is a plantation crop that has high economic value, especially because its seeds are used as the main raw material in the food and beverage industry. Rhizoctonia binucleate fungus and liquid organic fertilizer can prevent stem rot disease in vanilla plants by competing directly with disease-causing pathogens. The aim of this research was to determine the effect of administering Rhizoctonia binucleate fungus and liquid organic fertilizer on the development of stem rot disease in vanilla plants (Vanilla planifolia Andrews). The treatments carried out were designed in a factorial experiment in a complete Randomized Block Design. Liquid organic fertilizer doses: 0, 5, 10, 15, 20, and 25 ml/plant, 5g Rhizoctonia binucleate (BNR) dose, without BNR and BNR treatment, giving Fusarium oxysporum f. sp. vanillae 5 grams and without giving Fusarium oxysporum f. sp. vanillae. The results showed that administration of Rhizoctonia binucleate and Fusarium oxysporum f. sp. vanillae (R1), Fusarium oxysporum f. sp. vanillae (R2) and liquid organic fertilizer (P) have a significant effect on the growth of vanilla seedlings, namely on the number of leaves parameter, while on the parameters of plant height, leaf area, fresh plant stover weight, plant dry stover weight, fresh root weight and root dry fruit, these interactions do not have a significant effect.